2015
DOI: 10.14483/udistrital.jour.calj.2015.2.a01
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, Attitudes, and Reflections of EFL Pre-service Teachers when Exploring Critical Literacy Theories to Prepare and Implement Critical Lessons.

Abstract: <p>Foreign language teaching and learning is an issue of high relevance nowadays in Colombia. Unfortunately, language teaching has often been reduced to the mastery of language structures, disregarding the vast number of possibilities that language teaching provides to involve students in the discussion and analysis of issues that affect their everyday life. Shifting language teaching toward this goal, however, has to start in language teacher preparation programs. To gain a better understanding of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…In-depth self-reflection assists PTs in examining the deeply rooted and often unconscious beliefs they bring into their teacher training and future classrooms. This self-reflection also helps them speculate on issues of language ideologies, linguistic diversity, linguistic discrimination in their lives and larger society, and further how validating students’ languages in school impacts students’ lives (see Bartolomé, 2004; Gutierrez, 2015). The findings of this study suggest that (1) PTs’ contradictory language ideologies revealed entrenched deficit ideologies to minoritized and stigmatized languages and language users, (2) the realization of the intertwined relationship between language ideologies and their identities would be a stepping-stone of becoming an equity-minded educator, and (3) there is a need to provide more opportunities for personal exposure to linguistic diversity in teacher education programs.…”
Section: Discussion and Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In-depth self-reflection assists PTs in examining the deeply rooted and often unconscious beliefs they bring into their teacher training and future classrooms. This self-reflection also helps them speculate on issues of language ideologies, linguistic diversity, linguistic discrimination in their lives and larger society, and further how validating students’ languages in school impacts students’ lives (see Bartolomé, 2004; Gutierrez, 2015). The findings of this study suggest that (1) PTs’ contradictory language ideologies revealed entrenched deficit ideologies to minoritized and stigmatized languages and language users, (2) the realization of the intertwined relationship between language ideologies and their identities would be a stepping-stone of becoming an equity-minded educator, and (3) there is a need to provide more opportunities for personal exposure to linguistic diversity in teacher education programs.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…She also found, however, that the more contact teachers had with ELs, the more likely they were to hold positive beliefs about them. Noting this need for more exposure and training, teachers could, with a reformulation of their beliefs, plan and advocate for more equitable opportunities for their students (e.g., Bartolomé, 2004; Gutierrez, 2015). However, research in this area is still scant (e.g., Harrison & Lakin, 2018, as an exception).…”
Section: Guiding Frameworkmentioning
confidence: 99%
“…What is beneath reflective practice: Skills, goals and limitations On the road to selfregulation: Gauging pivotal change in the language classroom is facilitated by affective factors including the desire to learn and improve and also by cognitive factors such as critical awareness and existing beliefs (Clavijo, Guerrero, Torres, Ramírez, & Torres, 2004;Gutiérrez, 2015;Phipps, 2009). Although 60% of participants revealed this type of need, the fact that they are somewhat aware may help them to encounter appropriate learning strategies to monitor their language learning and to strive for further professional development opportunities.…”
Section: Weaknesses and Strengths Of In-service English Teachersmentioning
confidence: 99%
“…Hence, the more professional development opportunities that both pre-and in-service teachers may have, the better equipped they will be to meet the demands that the teaching of new generations of learners pose. In this way, they are also able to visualize and broaden the scope of what the act of language teaching entails which, in Colombia, has often been reduced to the mastery of language structures (Gutiérrez, 2015). Such a view echoes the principles of the Organization for Economic Co-operation and Development (OECD, 2009) in that they call for the involvement of education systems and agents (including policy makers and stakeholders) to seek and provide teachers with opportunities for professional development in order to maintain a high standard of teaching and to retain a high-quality teacher workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies were oriented towards pre-service teachers' beliefs (I. Aguirre, 2014;Castellanos, 2013;Fajardo, 2013;Gutiérrez, 2015;Higuita & Díaz, 2015), perceptions about ideological influence (A. Cárdenas & Suárez, 2009;Viáfara, 2016), the development of their research skills (M. L. Cárdenas, Nieto, & Martin, 2005;Posada & Garzón, 2014), the improvement of linguistic or intercultural competencies (Castro & López, 2014;Fajardo & Miranda, 2015;Franco & Galvis, 2013;Ramos, 2013;Viáfara, 2008), their reflections on language teaching (Castillo & Díaz, 2012;Morales, 2016); also, some others propose changes for the curriculum for language teacher education programs in regard to the teaching practicum (J.…”
Section: Studies In Colombiamentioning
confidence: 99%